An Analysis of Gender Bias Reflected in Short Animation Movies: Shattered, Witches, and Purl - Saiful Khaki (Metaphor, 2023)
Gender bias is preference or unfair treatment of someone based on their gender. Even though our society has made great progress in terms of gender equality, there are still many cases of gender bias that occur. This journal will explore some examples of gender bias that still exist in our daily lives. There are two problems discussed in this research, those are; how is gender bias reflected in the short animation movies: Shattered, Witches, and Purl and how is women’s struggle as the result of gender bias reflected in the short animation movies: Shattered, Witches, and Purl. The research uses descriptive qualitative method to analysed the short animation movies: Shattered, Witches, and Purl as the objective research. The collecting data of the research method includes watching and reading, identifying, classifying, and selecting. The analysing data of the research method by used displaying, explaining, and interpreting. In this research, the researchers found the element of gender bias. It is reflected through the movies that women are disproportionately impacted negatively by the practice of gender bias. Stereotypes that have existed for a long time contribute to gender bias. Women are referred to as feminists, while men are referred to as masculine. Such generalizations in some cases cause ladies to need to wear something attractive to be delightful. Female robots in Shattered are shown to have hips and chests that are large. It is a common misconception that beautiful women are. Despite the fact that these stereotypes can be harmful to women because they are vulnerable to both physical and non-physical sexual violence.